Hallstatt Culture in Croatia - current state and short review of recent research - Potrebica, Hrvoje (2006)
The lecture presented current state and short review of recent research in the Hallstatt Culture in Croatia to the participants of the round table Sopron- Kultur-, Wirtschafts und Landschaftsgeschichte eines ostmitteleuropäischen Zentralraumes.